Spatial variability in rates of net primary production (NPP) and onset of the spring bloom in Greenland shelf waters. (November 2021) - Vernet, Maria; Ellingsen, Ingrid; Marchese, Christian; Bélanger, Simon; Cape, Mattias; Slagstad, Dag; Matrai, Patricia A.
Graphical abstract: Variability in the date of phytoplankton bloom initiation in Greenland continental shelf for the period 2008–2017. The bloom start date is estimated when the change in daily production exceeds 0.2 g C m −2 d -1 . The shelves have been divided in 7 regions based on the Net Primary Production distribution in the coastal waters around Greenland: counter-clockwise, SouthEast (SE ), Central East (CE ), NorthEast (NE ), North (N ), NorthWest (NW ), Central West (CW ) and SouthWest (SW). Bloom initiation shows a strong north–south gradient, beginning in April in the southern regions (SE and SW ) and in July in the Arctic Ocea (N ). Sea ice presence (or lack thereof) appear to primarily determine the consistency in the timing of bloom initiation in each region. Highlights: Rates of annual NPP show a strong south-north gradient, with higher NPP rates observed in the North Atlantic water-influenced southern regions, with up to a factor of 3 decrease in NPP towards the north, in the western Eurasian Basin of the Arctic Ocean. Bloom initiation shows a strong south-north gradient, beginning in April in the southern regions and late June in the Arctic Ocean. An average 55% to 75% of the annual production can be exported to depth, higher in Arctic and sub-Arctic regions, suggesting Greenland shelf waters have a potential for high carbon export to depth. Abstract: Greenland extends from 60° to 83° N, with 80% of its land mass covered by the Greenland Ice Sheet (GrIS). This extensive latitudinal gradient is associated with concomitant environmental gradients that impact the biogeochemical properties of its coastal waters. Although the Greenland fjords have been the subject of intense study, less is known of the productivity in the continental shelves, regions that support local fisheries and influence fjord oceanography. This study provides a large-scale overview of annual net primary production rates (NPP) and their spatial variability in 7 regional shelves around Greenland, over the last decade (2008–2017), with special emphasis on spring bloom initiation. NPP is estimated by two independent approaches already established as best for estimating Arctic productivity: a physically-biologically coupled, regional 3D ocean model (SINMOD) and a spectrally-resolved, light-photosynthesis model of primary production (UQUAR-Takuvik model) that is applied to satellite observations of phytoplankton chlorophyll a, which is derived from ocean color remote sensing (OCRS). Both OCRS and SINMOD provide similar estimates of the timing and rates of productivity in Greenlandic waters, when compared with scarce field estimates. Bloom initiation shows a strong south-north gradient, beginning in April in the southern regions and late June in the Arctic Ocean. OCRS-modeled NPP highlights the effect of sea ice presence on bloom initiation; this method depicts the start of the bloom consistently later, by up to 13 days on average, than SINMOD-modeled NPP estimates. In contrast, numerical modeling is able to detect early phytoplankton growth in Greenland shelves, particularly underneath seasonal sea ice. Rates of annual NPP show a strong south-north gradient, with higher NPP rates observed in the North Atlantic water-influenced southern regions, with up to a factor of 3 decrease in NPP towards the north, in the western Eurasian Basin of the Arctic Ocean. Annual NPP varies from 78.3 ± 12.3 g C m −2 yr −1 and 80.3 ± 18.7 g C m −2 yr −1 in the southern regions to 24.7 ± 3.9 g C m −2 yr −1 in the Arctic Ocean. In each region, sea ice distribution and timing of formation and retreat affect location and timing of seasonal productivity with earlier and higher NPP offshore, moving inshore towards the summer. An average 55% to 75% of the annual production is estimated to be exported to depth, higher in Arctic and sub-Arctic regions, suggesting Greenland shelf waters have a potential for high carbon export to depth and relatively less carbon associated with the microbial food web.